Screening of polyamines in selected Malaysian local plants - Mohd. Halifah, Nor Fadhlina; Abdul Ghani, Radiah (2014)
Polyamines are an aliphatic compound which has various biological roles in the body. The imbalance of this compound in the body could lead to several diseases such as cancer. Since one of the sources is through diet intake, it is essential to obtain information on polyamines content in the food and natural source products which can be found in fruits, vegetables and herbs. The aim of this study is to extract and quantify the polyamine content in selected Malaysian plants pegaga (Centella asiatica), pecah beling (Strobilanthes crispus), kesum leaves (Polygonum minus), red spinach (Amaranthus gangeticus) and graviola (Annona Muricata) . Then, to classify the classes of polyamines among them. Polyamines were extracted by using perchloric acid based on Smith and Davis (1984) with modification. Then, extracted polyamines from selected samples were dansylated with dansyl chloride before analyzed using HPLC. Putrescine was found in all samples except for fresh C. asiatica. Putrescine was detected in high quantity in fresh P. minus leaves extraction (1526.72nmoles) compared to others. While, the lowest spermidine present among all sample is only in A. muricarata extract juice (0.57 nmoles). Whereas for spermine, fresh S. crispus leaves extraction shown the highest concentration which is 64.99 nmoles followed by fresh P.minus leaves extraction (83.81 nmoles) and fresh A. gangeticus leaves extraction (111.36 nmoles). A. muricata extract juice contain low level of polyamine (6.81 nmoles) followed by fresh C. asiatica leaves extraction which has intermediated level of polyamines which is 163.92 nmoles. Fresh S. crispus leaves extraction (214.72 nmoles), fresh A. gangeticus leaves extraction (403.10 nmoles) and fresh P. minus leaves extraction (1851.69 nmoles) contain high concentration of total polyamines. In conclusion, this study revealed that the polyamines detected in C. asiatica, S. crispus, P. minus , A. gangeticus and A. muricata . Highest total polyamine content is detected in S. crispus followed by A. gangeticus and P. minus,the lowest which falls under low category is detected in A. Muricata juice while the low and intermediate level of polyamines detected in C. asiatica .